Preparation and Characterization of Ethanol Extract of Spons Xestospongia sp. - Indalifiany, Astrid; Sahidin, Sahidin; Wahyuni, Wahyuni; Fristiohady, Adryan; Sadarun, Baru; Andriani, Rina; Aspadiah, Vica Aspadiah; Naimah, Naimah (Universitas PGRI Adi Buana, Surabaya, 2021)
Background: Xestospongia sp. is a species of the Demospongiae class that can be used as a medicinal substance. Xestospongia sp is known to have various activities such as anticancer, antibiotic, anti-fungal, cardiotonic, and antimalarial. One of the ways to make the formulation of natural ingredients is the phytosome vesicle technique. This method can be used to increase the penetration of compounds through cell membranes, increase their absorption and increase its bioavailability in the body. Objective: The aim of this study was to obtain the optimum phytosome composition in the ethanol extract of Xestospongia sp. and phosphatidylcholine with approprite vesicle characteristics. Methods: The preparation was carried out by varying the extract and phosphatidylcholine with a thin layer hydration method at a ratio of 1:1, 1:2, 2:1, and 2:2 and and phytosome characterization was carried out in each of these formulas to obtain the optimal formula. Results: In this study, the optimum phytosome formula has met the criteria based on morphological test parameters using an optical microscope obtained by spherical morphology, stability of physical appearance observations stored at 2oC-8oC ± 1oC temperature, pH measurement using a pH meter obtained a pH value of 4.20, and particle size determination using the Particle Size Analyzer (PSA) obtained a particle size of 180.6 nm and particle distribution value (IP) of 0.133. Conclusion: Composition of the optimum phytosome formula in the ratio of extract and phosphatidylcholine 1: 1 with the LUV phytosome category (Large Unilamellar Vesicle)